Peningkatan Efektivitas Kerja Guru Melalui Penguatan Kepemimpinan Melayani Dan Kepuasan Kerja : (Studi Empiris Menggunakan Metode Korelasional Dan Analisis Sitorem Pada Guru SMK Swasta Di Kecamatan Bogor Barat) - Setyo Ramdhani; Sumardi Sumardi; Eka Suhardi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research is classified as correlational research consisting of two independent variables, namely Servant Leadership and Job Satisfaction and one dependent variable Teacher Work Effectiveness. The population in the study was 305 teachers of private vocational schools in West Bogor Sub-district, with a sample size of 173 teachers, whose determination used the Slovin formula and used Proportional Random Sampling. Data were collected using instruments in the form of questionnaires and analyzed by descriptive analysis and inferential statistics and analyzed SITOREM. The results showed three positive relationships. First, there is a positive relationship between Servant Leadership and Teacher Work Effectiveness with a correlation coefficient value of 0.373. Second, there is a positive relationship between job satisfaction and teacher work effectiveness with a correlation coefficient value of 0.740. Third, there is a positive relationship between Servant Leadership and Job Satisfaction together with Teacher Work Effectiveness with a correlation coefficient value of 0.750. And based on the results of the SITOREM analysis, it shows that there are several indicators that must be improved and several indicators must be maintained. Indicators that must be improved include the implementation of evaluations, self-adjustment to the environment, humility, trust, courage, the job itself, supervision, promotion. Thus it can be concluded that Teacher Work Effectiveness can be improved through strengthening Servant Leadership and Job Satisfaction both partially and jointly.